Product Quality Signaling in Experimental Markets - Miller, Ross M.; Plott, Charles R. (Econometrica, 1985)
In a series of eleven markets, sellers possessed products that were exogenously designated as either grade "regular" or grade "super." Supers were valued more by buyers but grade could not be observed by buyers prior to purchase. Sellers could add costly units of quality to their products that were observable and valued by buyers. The data are analyzed with perfect information models, signaling equilibrium models, and pooling models. A variety of behaviors are observed across the eleven markets. Signaling is observed in most markets with some markets approaching the most efficient signaling equilibrium. Pooling or partial pooling occurs in a few markets. The performance seems to be sensitive to the relative cost of signaling and the market institutional setting.